Influence of electro-ejaculator on serum concentrations of acute phase proteins and bone metabolism biomarkers in male dromedary camels (Camelus dromedarius). Issue 1 (1st January 2018) - Tharwat, Mohamed; Al-Sobayil, Fahd
ABSTRACT: This study was carried out to evaluate the effect of electroejaculation (EEJ) on the serum concentrations of the acute phase proteins (APPs) serum amyloid A (SAA) and haptoglobin (Hp), and on the bone metabolism biomarkers osteocalcin (OC), bone-specific alkaline phosphatase (b-ALP) and pyridinoline cross-links (PYD). Twenty sexually mature apparently healthy male camels were assigned to EEJ. Parallel, 8 naturally mated male camels were enrolled as a control group. Three blood samples were collected from each camel: just before (T0), directly after (T1) and 24 h after (T2) EEJ or natural mating camels. The serum concentrations of the APPs and bone biomarkers were determined. The serum concentrations of SAA increased significantly at T1 compared to T0. In none of the 2 groups was the serum concentration of Hp differed significantly. The serum concentrations of OC increased significantly at T1 compared to T0. In none of the 2 groups was the serum concentration of b-ALP differed significantly among T0, T1 and T2. It is concluded that acute phase reaction, manifested by significant increases of SAA, had occurred in male camels as a result of EEJ. In addition, EEJ increased serum concentration of the bone formation biomarker OC.